Field evaluation of diagnostic performance of malaria rapid diagnostic tests in western Kenya. (December 2016) - Wanja, Elizabeth; Kuya, Nickline; Moranga, Collins; Hickman, Mark; Johnson, Jacob; Moseti, Carolyne; Anova, Lalaine; Ogutu, Bernhards; Ohrt, Colin
Abstract Background Malaria continues to be a major burden in the endemic regions of Kenya. Health outcomes associated with case management are dependent on the use of appropriate diagnostic methods. Rapid diagnostic tests (RDTs) have provided an important tool to help implement the WHO recommended parasite-based diagnosis in regions where expert microscopy is not available. One of the questions that must be answered when implementing RDTs is whether these tests are useful in a specific endemic region, as well as the most appropriate RDT to use. Data on the sensitivity and specificity of RDT test kits is important information to help guide test selection by national malaria control programmes. Methods This study evaluated the diagnostic performance of RDTs including First Response (FR), CareStart (CS), SD Bioline (SD), and Binax Now (BN). The performance of these malaria kits was compared to microscopy, the gold standard, for the detection of malaria parasites. The malaria RDTs were also compared to PCR which is a more sensitive reference test. Five-hundred participants were included in the study through community screening (50 %) and testing suspected malaria cases referred from health facilities. Results Of the 500 participants recruited, 33 % were malaria positive by microscopy while 51.2 % were positive by PCR. Compared to microscopy, the sensitivity of eight RDTs to detect malaria parasites was 90.3–94.8 %, the specificity was 73.3–79.3 %, the positive predictive value was 62.2–68.8 %, and the negative predictive value was 94.3–96.8 %. Compared to PCR, the sensitivity of the RDTs to detect malaria parasites was 71.1–75.4 %, the specificity was 80.3–84.4 %, the positive predictive value was 80.3–83.3 %, and the negative predictive value was 73.7–76.1 %. The RDTs had a moderate measure of agreement with both microscopy (>80.1 %) and PCR (>77.6 %) with a κ > 0.6. Conclusion The performance of the evaluated RDTs using field samples was moderate; hence they can significantly improve the quality of malaria case management in endemic regions in Kenya by ensuring appropriate treatment of malaria positive individuals and avoiding indiscriminate use of anti-malarial drugs for parasite negative patients.